THE RELATIONSHIP BETWEEN EMOTIONAL ITELLIGENCE AND SELF-CONTROL IN PIK-R MEMBER HIGH SCHOOL/VOCATIONAL SCHOOL STUDENTS - Al Fikri, Dimas Rifki; Widyastuti, Widyastuti (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to determine the relationship between emotional intelligence and self-control in high school/vocational school students who are members of the Youth Information and Counseling Center (PIK-R) organization. Method: This research uses a quantitative approach with a correlational survey design. The research sample consisted of 228 students aged 15-18 years who were active in PIK-R in the last 6 months. The sampling used is purposive sampling. Data was collected using two measurement scales, namely the Emotional Intelligence scale consisting of 30 items with a reliability (α) of 0.813, and the Self-Control Scale consisting of 30 items with a reliability (α) of 0.748. Data analysis was carried out by Spearman's Rho correlation test using SPSS software version 25. Results: The results of the research showed a significant correlation between Self-Control and Emotional Intelligence of High School/Vocational High School Students with PIK-R (r=0.724*** p0.724). There were results that emotional intelligence had an effective contribution to self-control of R2 = 0.525, suggesting that emotional intelligence explained 52.5% of the self-control variance. Novelty: This research aims to determine the relationship between emotional intelligence and self-control in high school/vocational school students who are members of the Youth Information and Counseling Center (PIK-R) organization.